"THE ROLE OF EDUCATION IN FORMING THE LIFE STRATEGY OF YOUNG PEOPLE" (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Formation of the life strategy of the young generation and the place of education in it. The influence of the family on life orientation-education Conclusion List of references Introduction Identification of life strategies of young people involves taking into account external factors that influence the change in the life of young people and internal ones, which are presented in the form of life plans and value orientations.